Influence of Problem Based Learning on Students Critical Thinking Ability - Dewi Wahyuningsih; Muh. Yunus; Muh. Ilyas Thamrin Tahir; Muqtakdir Nurfalaq Syarif (STKIP Taman Siswa Bima, 2023)
Problem based learning can help them become active and independent students and improve their ability to think and solve problems. This study aims to: 1) To assess fifth-grade students' critical thinking abilities at SDN Pannara Makassar City without making use of problem based learning methods. 2) To assess the critical thinking abilities of fifth-grade students at SDN Pannara Makassar City, utilized was the problem based learning approach. 3) To determine the influence of problem based learning methods on students' critical thinking skills between social studies learning outcomes of students who were given the problem based learning method and those who were not given the problem based learning method. Quasi-experimental research is this kind. Non-equivalent pretest-posttest study design with two classes is used in this investigation. Specifically, there are two classes: control and experimental. In the trial lesson, the traditional lecture method is used for learning, and in the experimental lesson, use of the problem based learning approach. From the data obtained, it can be seen that the influence of problem based learning methods can improve students' critical thinking skills. The results of inferential statistical analysis using covariance analysis (ANCOVA) obtained a Sig.count value of 0.000 with α = 0.05. The analysis revealed that the Sig.count value was greater than α (0.000 > 0.05), so that Ho was rejected and H1 was accepted. As a result, it is possible to draw the conclusion that using problem based learning techniques in addition to traditional learning can help students' critical thinking skills.